2010
DOI: 10.3390/ijerph7124169
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 2002 Delaware Smoking Ordinance on Heart Attack and Asthma

Abstract: Abstract:In the United States, smoking is the leading cause of death -having a mortality rate of approximately 435,000 people in 2000-accounting for 8.1% of all US deaths recorded that year. Consequently, we analyzed the Delaware Hospital Discharge Database, and identified state and non-state residents discharged with AMI or asthma for the years 1999 to 2004. Statistical data analysis compared the incidence of AMI or asthma for each group before (1999-2002) and after (2003-2004) the amendment. As a result, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
(18 reference statements)
0
17
1
2
Order By: Relevance
“…This implies that almost 1900 emergency admissions for asthma were prevented in England during the first year after legislation was introduced and a similar number of emergency admissions for asthma were prevented in the subsequent 2 years. The decrease in emergency admissions for asthma among adults was lower than that observed in other countries 17–19 22. This may be attributable in part to the differences in the specification of the long-term trend between these studies and ours.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This implies that almost 1900 emergency admissions for asthma were prevented in England during the first year after legislation was introduced and a similar number of emergency admissions for asthma were prevented in the subsequent 2 years. The decrease in emergency admissions for asthma among adults was lower than that observed in other countries 17–19 22. This may be attributable in part to the differences in the specification of the long-term trend between these studies and ours.…”
Section: Discussioncontrasting
confidence: 77%
“…Only a few studies have examined impacts in adults and collectively the findings from these studies are inconclusive. For example, studies in Ireland,19 Kentucky17 and Delaware22 reported statistically significant reductions in hospital asthma admissions after the introduction of smoke-free legislation of 40%, 24% and 5% respectively, while a New Zealand18 study reported a non-statistically significant decline of 16%. Moreover some of these studies have limited statistical power due to small study populations and it is unclear whether underlying long-term trends in asthma admissions were properly controlled for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the nine studies carried out in the general population[ 34 , 42 , 45 , 46 , 51 , 60 , 61 , 64 , 75 ], six of them (66.7%) were quasi-experimental[ 42 , 45 , 46 , 51 , 60 , 61 ], and, with the exception of one[ 61 ], all were performed in comprehensive SFL locations. In eight studies (88.9%), admission rates for asthma (both hospital and non-hospital admissions) significantly declined with a range of 5.0%[ 60 ] to 31.0% (the latter figure was for Caucasians in Texas[ 45 ]). In addition, a significant annual rate of reduction of -0.35 [95% confidence interval (CI) -0.53 to -0.018] in hospital asthma admissions was obtained in the sole study on partial SFL[ 61 ] when it compared SFL in restaurants versus public areas and workplaces over the ten-year study period.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which these policies have a pro- or anti-equity impact is important to know, given the widening racial gap in AMI. Studies of the impact of smoke-free policy on AMI in the U.S. often do not address this question, or are unable to due to small numbers within racial/ethnic subgroups of the study population (Bartecchi et al, 2006; Bruintjes et al, 2011; Gupta et al, 2011; Hahn et al, 2011; Hurt et al, 2012; Moraros et al, 2010). Of the available literature, Dinno & Glantz (2009) found no interaction between clean indoor air laws and race/ethnicity for either current smoking status or daily cigarette consumption, thus concluding that there was an equal affect across groups.…”
Section: Introductionmentioning
confidence: 99%